Comparison of oral versus intravenous application of tranexamic acid in total knee and hip arthroplasty: A systematic review and meta-analysis. (September 2017) - Zhang, Lu-kai; Ma, Jian-xiong; Kuang, Ming-jie; Zhao, Jie; Wang, Ying; Lu, Bin; Sun, Lei; Ma, Xin-long
Abstract: Background: Tranexamic acid (TXA) is regarded as one of the most important drugs in reducing blood loss and hemoglobin (Hb) drop after total knee arthroplasty (TKA) or total hip arthroplasty (THA). Treatment with tranexamic acid (TXA) by intravenous application has been discussed extensively. Recently, several studies have reported that oral administration has an effect on blood sparing. Therefore, we performed a meta-analysis to investigate the efficacy and safety between oral TXA and intravenous TXA (IV-TXA) for blood sparing in total knee and hip arthroplasty. Methods: Randomized controlled trials (RCTs) or retrospective cohort studies (RCSs) about relevant research were searched for by using PubMed (1996–April 2017), Embase (1980–April 2017), and the Cochrane Library (CENTRAL, April 2017). Five studies that compared oral with IV administration of TXA were included in our meta-analysis. Meta-analysis results were collected and analyzed by the software Review Manager 5.3 (Copenhagen: The Nordic Cochrane Center, The Collaboration, 2014). Results: Five studies containing 3474 patients met the inclusion criteria. Our pooled data analysis indicated that oral TXA was as effective as the IV-TXA in terms of the average Hb drop ( P  = 0.88), total Hb loss ( P  = 0.57), total blood loss ( P  = 0.42), transfusion rate ( P  = 0.16), complications ( P  = 0.61), and length of hospital stay (P = 1.00). Conclusions: Compared with the IV-TXA method, oral TXA shows similar blood-sparing efficacy for preventing hemoglobin drop, total hemoglobin loss, and total blood loss following TKA or THA. In addition, no significant differences of transfusion rate, complications, or length of hospital stay were found between the 2 groups. However, because of the limited number of included studies, more studies of high quality are needed to further identify the optimal administration time for oral TXA. Highlights: We made this meta-analysis to compare of oral with IV administrations of TXA following TKA and THA. Oral TXA and IV TXA benefit similarly for knee and hip function improvement. Oral TXA will not increase the risk of complications. Oral TXA is economical and convenient to use compared to IV form.